Public relations and religion in American history - Lamme, Margot Opdycke, author.
1 online resource
Keywords: "This study of American public relations history traces evangelicalism to corporate public relations via reform and the church-based temperance movement. It encompasses a leading evangelical of the Second Great Awakening, Rev. Charles Grandison Finney, and some of his predecessors; early reformers at Oberlin College, where Finney spent the second half of his life; leaders of the Woman's Christian Temperance Union and the Anti-Saloon League of America; and twentieth-century public relations pioneer Ivy Ledbetter Lee, whose work reflecting religious and business evangelism has not yet been examined."